2013
DOI: 10.3389/fimmu.2013.00403
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell Plasticity in Tumor-Conditioned Skin: CD14+ Cells at the Cross-Roads of Immune Activation and Suppression

Abstract: Tumors abuse myeloid plasticity to re-direct dendritic cell (DC) differentiation from T cell stimulatory subsets to immune-suppressive subsets that can interfere with anti-tumor immunity. Lined by a dense network of easily accessible DC the skin is a preferred site for the delivery of DC-targeted vaccines. Various groups have recently been focusing on functional aspects of DC subsets in the skin and how these may be affected by tumor-derived suppressive factors. IL-6, Prostaglandin-E2, and IL-10 were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 64 publications
1
21
1
Order By: Relevance
“…This would also fit with our observation of high levels of IL6 released by single-cell suspensions of LN þ . We and others have reported a phenotypically similar subset in a range of solid tumor types (36)(37)(38)(39). PD-L1 is expressed by the primary cervical tumor cells and its receptor PD-1 is often expressed by T cells infiltrating the primary tumor (40), similar to the results we obtained for LN þ .…”
Section: Discussionsupporting
confidence: 90%
“…This would also fit with our observation of high levels of IL6 released by single-cell suspensions of LN þ . We and others have reported a phenotypically similar subset in a range of solid tumor types (36)(37)(38)(39). PD-L1 is expressed by the primary cervical tumor cells and its receptor PD-1 is often expressed by T cells infiltrating the primary tumor (40), similar to the results we obtained for LN þ .…”
Section: Discussionsupporting
confidence: 90%
“…We found that following migration across 22qDS+SZ iBBB monolayer, monocytes significantly decreased thrombomodulin (TM, CD141) expression ( Figure 4D-E). As TM is known to be an anti-inflammatory molecule expressed on both immune cells and the luminal endothelium to inhibit immune cell adherence and extravasation (Loghmani & Conway, 2018;van de Ven et al, 2013;Xu et al, 2015), our findings indicate that the 22qDS+SZ BBB has a promigratory effect on immune cells.…”
Section: Qds Bbb Promotes Monocyte Migration and Activationmentioning
confidence: 59%
“…[30][31][32] IL-6 expression in PCa has been attributed to both stromal and tumor cells 33 and the influences of various tumor-derived factors, such as IL-6 and IL-10, on DC differentiation from myeloid cells have been previously studied. [34][35][36][37] Furthermore, tumor-derived soluble factors have also been shown to affect DC function, 38,39 Fibroblast-derived IL-6 has also previously been shown to effect the differentiation of monocytes into macrophages (rather than DCs). 40,41 However, our experiments clearly demonstrate that in early PCa, IL-6 expression is higher in PCaSt than PCaEp, indicating that stromal cells are the dominant cell type to influence myeloid cell differentiation.…”
Section: Discussionmentioning
confidence: 99%